T-Cell-Replete Versus ex vivo T-Cell-Depleted Haploidentical Haematopoietic Stem Cell Transplantation in Children With Acute Lymphoblastic Leukaemia and Other Haematological Malignancies - Kleinschmidt, Katharina; Lv, Meng; Yanir, Asaf; Palma, Julia; Lang, Peter; Eyrich, Matthias (Frontiers in Pediatrics, 2021)
Allogeneic haematopoietic stem cell transplantation (HSCT) represents a potentially curative option for children with high-risk or refractory/relapsed leukaemias. Traditional donor hierarchy favors a human leukocyte antigen (HLA)-matched sibling donor (MSD) over an HLA-matched unrelated donor (MUD), followed by alternative donors such as haploidentical donors or unrelated cord blood. However, haploidentical HSCT (hHSCT) may be entailed with significant advantages: besides a potentially increased graft-versus-leukaemia effect, the immediate availability of a relative as well as the possibility of a second donation for additional cellular therapies may impact on outcome. The key question in hHSCT is how, and how deeply, to deplete donor T-cells. More T cells in the graft confer faster immune reconstitution with consecutively lower infection rates, however, greater numbers of T-cells might be associated with higher rates of graft-versus-host disease (GvHD). Two different methods for reduction of alloreactivity have been established: in vivo T-cell suppression and ex vivo T-cell depletion (TCD). Ex vivo TCD of the graft uses either positive selection or negative depletion of graft cells before infusion. In contrast, T-cell-repleted grafts consisting of nonmanipulated bone marrow or peripheral blood grafts require intense in vivo GvHD prophylaxis. There are two major T-cell replete protocols: one is based on post-transplantation cyclophosphamide (PTCy), while the other is based on anti-thymocyte globulin (ATG; Beijing protocol). Published data do not show an unequivocal benefit for one of these three platforms in terms of overall survival, non-relapse mortality or disease recurrence. In this review, we discuss the pros and cons of these three different approaches to hHSCT with an emphasis on the significance of the existing data for children with acute lymphoblastic leukemia.